Remotely Operated Submarine Vehicle Control Using Fuzzy Logic - P. Palanichamy (Institute of Advanced Engineering and Science, 2017)
Submerged marine investigation still remains a puzzle. The motivation behind this paper is to address the issues in plan and improvement of submerged vehicles with hindrance shirking and moving help for administrator in marine condition utilizing fluffy rationale controller. A symmetrical, practical and little measured submerged Remotely Operated Vehicle (ROV) with three thrusters is intended for testing control calculation and execution of framework. Kinematics of the ROV is produced relating rate of revolution of thrusters with ROV'S straight and precise increasing speed. A near investigation of the framework's reaction for basic if-else rationale and with fluffy rationale controller for route is made and assessed. A Graphical User Interface (GUI) with live bolster is given to the administrator to more extensive scope of visual perception of submerged condition and navigational guide.